Differential trafficking of AMPA receptors following activation of NMDA receptors and mGluRs - Sanderson, Thomas M (BioMed Central, 2011)
The removal of AMPA receptors from synapses is a major component of long-term depression (LTD). How this occurs, however, is still only partially understood. To investigate the trafficking of AMPA receptors in real-time we previously tagged the GluA2 subunit of AMPA receptors with ecliptic pHluorin and studied the effects of NMDA receptor activation. In the present study we have compared the effect of NMDA receptor and group I mGluR activation, using GluA2 tagged with super ecliptic pHluorin (SEP-GluA2) expressed in cultured hippocampal neurons. Surprisingly, agonists of the two receptors, which are both able to induce chemical forms of LTD, had clearly distinct effects on AMPA receptor trafficking. In agreement with our previous work we found that transient NMDA receptor activation results in an initial decrease in surface GluA2 from extrasynaptic sites followed by a delayed reduction in GluA2 from puncta (putative synapses). In contrast, transient activation of group I mGluRs, using DHPG, led to a pronounced but more delayed decrease in GluA2 from the dendritic shafts. Surprisingly, there was no average change in the fluorescence of the puncta. Examination of fluorescence at individual puncta, however, indicated that alterations did take place, with some puncta showing an increase and others a decrease in fluorescence. The effects of DHPG were, like DHPG-induced LTD, prevented by treatment with a protein tyrosine phosphatase (PTP) inhibitor. The electrophysiological correlate of the effects of DHPG in the SEP-GluA2 infected cultures was a reduction in mEPSC frequency with no change in amplitude. The implications of these findings for the initial mechanisms of expression of both NMDA receptor- and mGluR-induced LTD are discussed.